Long-term Clinical Follow-up of Patients with Familial Hypomagnesemia with Secondary Hypocalcemia - Elvan Bayramoğlu; Melikşah Keskin; Zehra Aycan; Şenay Savaş-Erdeve; Semra Çetinkaya (Galenos Yayincilik, 2021)
Objective:Familial hypomagnesemia with secondary hypocalcemia (HSH) is an autosomal recessive disease caused by a mutation in the transient receptor potential melastatin 6 (TRPM6) gene and is characterized by selective magnesium malabsorption. Affected cases are usually diagnosed during infancy and usually present with seizures due to hypocalcemia and hypomagnesemia. Irreversible neurological deficits and arrhythmias can be observed without appropriate treatment. The aim was to evaluate the long-term follow-up of patients with genetically confirmed HSH.Methods:A total of six patients with HSH, two of whom were siblings, were included. Age at diagnosis, clinical, laboratory and follow-up data on admission were recorded. All 39 exons of the TRPM6 gene and flanking exon-intron junctions from genomic DNA were amplified and sequenced in all cases.Results:The median (range) follow-up duration was 12.1 (7.6-21.7) years. All cases were diagnosed in infancy. Four different mutations, three of which had not been previously reported, were detected in the TRPM6 gene. Treatment compliance was good and there were no severe complications in the long-term follow-up of cases. However, mental retardation, specific learning difficulty and attention deficit/hyperactive disorder were observed as comorbidities.Conclusion:Of the four different TRPM6 mutations in this small cohort, three had not been previously reported. The long-term prognosis of HSH appears to be good, given early diagnosis and good treatment compliance. This long-term follow-up and prognostic data and the three novel mutations will contribute to the published evidence concerning this rare condition, HSH, and it is hoped will prevent negative outcomes.